Unprovoked or provoked venous thromboembolism: not the prevalent criterion to decide on anticoagulation extension in clinical practice of various countries-the prospective, international, observational WHITE study - Palareti, Gualtiero; Bignamini, Angelo; Cini, Michela; Li, Young-Jun; Urbanek, Tomasz; Madaric, Juraj; Bouslama, Kamel; Sokurenko, German Y; Andreozzi, Giuseppe M; Matuška, Jiří; Mansilha, Armando; Barinov, Victor; et al. (Internal and emergency medicine, 2022)
The decision on treatment after a first venous thromboembolism (VTE) to prevent recurrences may be influenced by many factors. The prospective, observational, WHITE study aimed to analyze how this issue was tackled in every-day clinical practice in various countries, which have sensibly different socio-economic conditions and healthcare systems. Doctors active in 79 Internal or Vascular clinical centers in 7 countries (China, Czechia, Poland, Portugal, Russia, Slovakia, and Tunisia) enrolled VTE patients after the maintenance treatment phase. The present report analyzed information, collected in the central database, regarding the baseline characteristics, index events, type and duration of anticoagulant therapy and decision on post-maintenance treatment. From April 2018 to December 2020, 1240 patients were enrolled, 58% with an unprovoked index event. Direct oral anticoagulants (DOACs) were used in > 85% of all cases in China, Poland, Portugal, Russia and Czechia, in 52% in Slovakia and in no patient in Tunisia. The maintenance anticoagulation lasted in average approximately 6 months. Altogether, anticoagulation was stopped in 20%, extended in about 50%, regardless of whether the event was unprovoked or provoked and shifted to antithrombotics (mainly sulodexide or aspirin) in the remaining patients. In conclusion, some differences in VTE patient management were found between countries. The provoked/unprovoked nature of the index event, instead, was not the prevalent criterion to drive the decision on extension of anticoagulation, without large variations between countries. DOACs were the most widely used anticoagulant drugs, whereas > 25% of patients received antithrombotic drugs instead of anticoagulants as extended treatment.
Keywords: recidiva; Venous thromboembolism; Humans; rizikové faktory; Venous Thromboembolism; lidé; hemokoagulace; žilní tromboembolie; Anticoagulation; Blood Coagulation; Sulodexide; Antithrombotics; Aspirin; Recurrence; prospektivní studie; antikoagulancia; Anticoagulants; Risk Factors; Prospective Studies